2009
DOI: 10.1093/gerona/glp200
|View full text |Cite
|
Sign up to set email alerts
|

Low Serum Free Triiodothyronine Levels Mark Familial Longevity: The Leiden Longevity Study

Abstract: Compared with their partners, the group of offspring of nonagenarian siblings show a lower thyroidal sensitivity to thyrotropin. These findings suggest that the favorable role of low thyroid hormone metabolism on health and longevity in model organism is applicable to humans as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
5
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 20 publications
2
47
5
2
Order By: Relevance
“…Hypothyroidism can affect life expectancy by reducing the intensity of metabolism, body temperature and oxygen consumption, resulting in a decrease in the generation of free oxygen radicals and associated oxidative damage in cells. Subclinical hypothyroidism is associated with a reduction in mortality in women, which was found in families with long life expectancy and is due to polymorphism of the receptor to thyroid stimulating hormone (TSH) [19]. An important fact is that subclinical hypothyroidism is often recorded with type 2 DM [20].…”
Section: Neuroimmune and Neuroendocrine Communications: Aging Metabomentioning
confidence: 99%
“…Hypothyroidism can affect life expectancy by reducing the intensity of metabolism, body temperature and oxygen consumption, resulting in a decrease in the generation of free oxygen radicals and associated oxidative damage in cells. Subclinical hypothyroidism is associated with a reduction in mortality in women, which was found in families with long life expectancy and is due to polymorphism of the receptor to thyroid stimulating hormone (TSH) [19]. An important fact is that subclinical hypothyroidism is often recorded with type 2 DM [20].…”
Section: Neuroimmune and Neuroendocrine Communications: Aging Metabomentioning
confidence: 99%
“…relates with a lower mortality rate in people aged 85 plus [46,47,48,49], while lower fT4 levels correlate with good physical efficiency in elderly people (73-94 years of age) and a decreased risk of death [23,47,48,50].…”
Section: Niedoczynność Tarczycy W Podeszłym Wiekumentioning
confidence: 99%
“…W ostatnich latach ukazały się prace badające związek między długowiecznością a mniejszą aktywnością gruczołu tarczowego, z których moż-na wysnuć następujące wnioski: podwyższone stężenie TSH nie wiąże się z pogorszeniem sprawności, funkcji poznawczych czy depresją, koreluje zaś z obniżeniem umieralności u osób powyżej 85 r.ż. [46,47,48,49], natomiast niższe stężenia fT4 wiążą się z dobrą wydolnością fizyczną osób starszych (73-94 lata) oraz zmniejszonym ryzykiem zgonu [23,47,48,50].…”
Section: Hyperthyroidism In the Elderlyunclassified
“…The offspring had lower mortality risk, less diabetes, hypertension and CVD (14) . Furthermore, they had better lipid profiles (15) , higher insulin sensitivity (16) , slightly less circulating thyroid hormone (17) , slightly lower circulating cortisol (18) and positive outcome expectations (19) . Over the last two decades, studies in experimental animals have identified several cellular signalling pathways that partially explain the influence of genetic differences on longevity.…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%